Effects of epigenetic-based anti-cancer drugs in leukaemia and multiple myeloma cells - Jugová, Alžběta; Sustáčková, Gabriela; Legartová, Soňa; Stixová, Lenka; Kozubek, Stanislav; Bártová, Eva (Cell biology international, 2011)
Here, we focus on epigenetic changes in leukaemia and MM (multiple myeloma) cells. We show how the histone signature, DNA methylation and levels of select tumour-suppressor proteins can be affected by inhibitors of HDACs (histone deacetylases) and Dnmts (DNA methyltransferases). Both inhibitors, TSA (trichostatin A) and 5-AZA (5-azacytidine), have the ability to change the histone signature in a tumour-specific manner. In MM cells, we observed changes in H3K4 methylation, while in leukaemia cells, H3K9 methylation was especially affected by select inhibitors. Compared with normal peripheral blood lymphocytes, tumour cell samples were characterized by increased H3K9 acetylation, increased H3K4me2, H3K9me2 and HP1α (heterochromatin protein 1α) levels and specific changes were also observed for DNA methylation. Additionally, we showed that the tumour suppressor pRb1 (retinoblastoma protein) is more sensitive to epigenetic-based anti-cancer stimuli than p53. We have found significant decrease in the levels of pRb1 and p53 in both myeloma and leukaemia cells after HDAC inhibition.
Keywords: histony; DNA Methylation; homolog proteinu s chromoboxem 5; leukemie; protinádorové látky; metylace DNA; umlčování genů; epigeneze genetická; histondeacetylasy; Histone Deacetylase Inhibitors; Histone Deacetylases; Azacitidine; Multiple Myeloma; nádorový supresorový protein p53; azacytidin; Hydroxamic Acids; Leukemia; lidé; Retinoblastoma Protein; DNA Modification Methylases; inhibitory histondeacetylas; DNA modifikační methylasy; Humans; kyseliny hydroxamové; Chromobox Protein Homolog 5; Histones; Gene Silencing; mnohočetný myelom; retinoblastomový protein; Tumor Suppressor Protein p53; Antineoplastic Agents; Epigenesis, Genetic